2004
DOI: 10.1080/00288233.2004.9513582
|View full text |Cite
|
Sign up to set email alerts
|

Potassium in soil and pasture and leaching of cations on an allophanic soil in New Zealand

Abstract: Potassium chloride (KCl) was applied at 0, 150, 450, and 750 kg ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
1
14
0
4
Order By: Relevance
“…Morton et al (2004) also found the increasing rates of Cl leaching with application of K as compared to control. nearly all the leachates irrespective of the quality of irrigation water.…”
Section: The [So 4 ] and [Cl] Significantly Increased In All Thementioning
confidence: 75%
See 1 more Smart Citation
“…Morton et al (2004) also found the increasing rates of Cl leaching with application of K as compared to control. nearly all the leachates irrespective of the quality of irrigation water.…”
Section: The [So 4 ] and [Cl] Significantly Increased In All Thementioning
confidence: 75%
“…Robbins (1984) concluded that higher [K] were held in soil while Na leached down that reduced SAR and ESP. Potassium competes with other cations such as Ca and Mg for retention on soil exchange sites and high K levels may lead to increased leaching of Na and associated anions such as SO 4 and Cl (Morton et al, 2004).…”
Section: Chemical Composition Of Plant Tissuesmentioning
confidence: 99%
“…(1 yr (1 (Campkin 1985; Morton et al 2004;Monaghan et al 1999Monaghan et al , 2005Early et al 1998). …”
Section: K Buffer Capacitymentioning
confidence: 99%
“…Cow taste-strip trials carried out in October and November 2002 within a farmlet trial at Whareroa Research Centre in South Taranaki (described in Morton et al 2004) compared cow preference with pasture intake measured using the alkane technique at the same site (see below). The cow taste-strip trial was sited in two farmlet paddocks that had received 150 kg KCl ha -1 in March 2000.…”
Section: Farmlet Sitesmentioning
confidence: 99%
“…Sixteen Friesan × Jersey cows in each of two farmlets at Whareroa Research Centre in the third year (2002/03) of a trial designed to measure the effects of rate of K fertiliser on pasture and milksolids production (reported in Morton et al 2004) were used to measure the effect of the K content of pasture on pasture intake using the alkane technique (Dove & Mayes 1991 Extra KCl was applied to widen the difference in pasture K content between the two treatments. The cows were dosed twice daily at milking with capsules containing 356 mg C 32 alkane over a period of 10 days.…”
Section: Farmlet Sitesmentioning
confidence: 99%